2015
DOI: 10.3109/09638237.2015.1019054
|View full text |Cite
|
Sign up to set email alerts
|

Emerging mHealth and eHealth interventions for serious mental illness: a review of the literature

Abstract: Background Serious mental illness is one of the leading causes of disability worldwide. Emerging mobile health (mHealth) and eHealth interventions may afford opportunities for reaching this at-risk group. Aim To review the evidence on using emerging mHealth and eHealth technologies among people with serious mental illness. Methods We searched MEDLINE, PsychINFO, CINAHL, Scopus, Cochrane Central, and Web of Science through July 2014. Only studies reporting outcomes for mHealth or eHealth interventions, defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
235
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(258 citation statements)
references
References 78 publications
12
235
0
5
Order By: Relevance
“…24 A recent review of 46 studies reporting outcomes from digital health interventions in psychiatry found that emerging mobile technologies are highly feasible and acceptable for use among patients with SMI. 25 Unfortunately, digital health technologies are often developed without adequate evaluation of their validity and effectiveness. 26 A rigorous scientific approach to developing a new system based on formative and qualitative research with target users is time-consuming and often impractical to conduct in the field, considering the rapid evolution of technologies and their continuously changing role in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…24 A recent review of 46 studies reporting outcomes from digital health interventions in psychiatry found that emerging mobile technologies are highly feasible and acceptable for use among patients with SMI. 25 Unfortunately, digital health technologies are often developed without adequate evaluation of their validity and effectiveness. 26 A rigorous scientific approach to developing a new system based on formative and qualitative research with target users is time-consuming and often impractical to conduct in the field, considering the rapid evolution of technologies and their continuously changing role in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…34 These have included, for example, developments with mobile applications (e.g smartphones) to assess mood functioning and symptoms, 35 online psychological therapies, 36 interactive text messages, 37 computerised interventions, 38 and wearable technologies that offer real time feedback on wellbeing and functioning such as activity and sleep quality. [39][40] Digital interventions could be a useful way to offer time and cost effective approaches to reach and engage with larger populations, including those who might be less willing or able to access standard services because of geography and travel burden, or where flexible modes of access and/or privacy are prioritised.…”
Section: -29mentioning
confidence: 99%
“…A recent systematic review concludes that Internet and mobile-based interventions for psychosis seem to be cost-effective, accessible, acceptable, feasible and have the potential to improve clinical and social outcomes [16]. An ulterior review that includes studies carried out in 12 different countries supports the feasibility and acceptability of emerging mHealth and eHealth interventions among people with serious mental illness (including schizophrenia, schizoaffective disorder and bipolar disorder) [17].…”
Section: Use Of Digital Technology In Schizophrenia and Related Disormentioning
confidence: 99%